Face adaptation aftereffects reveal anterior medial temporal cortex role in high level category representation - Furl, N. (Academic Press, 2007)
Previous studies have shown reductions of the functional magnetic resonance imaging (fMRI) signal in response to repetition of specific visual stimuli. We examined how adaptation affects the neural responses associated with categorization behavior, using face adaptation aftereffects. Adaptation to a given facial category biases categorization towards non-adapted facial categories in response to presentation of ambiguous morphs. We explored a hypothesis, posed by recent psychophysical studies, that these adaptation-induced categorizations are mediated by activity in relatively advanced stages within the occipitotemporal visual processing stream. Replicating these studies, we find that adaptation to a facial expression heightens perception of non-adapted expressions. Using comparable behavioral methods, we also show that adaptation to a specific identity heightens perception of a second identity in morph faces. We show both expression and identity effects to be associated with heightened anterior medial temporal lobe activity, specifically when perceiving the non-adapted category. These regions, incorporating bilateral anterior ventral rhinal cortices, perirhinal cortex and left anterior hippocampus are regions previously implicated in high-level visual perception. These categorization effects were not evident in fusiform or occipital gyri, although activity in these regions was reduced to repeated faces. The findings suggest that adaptation-induced perception is mediated by activity in regions downstream to those showing reductions due to stimulus repetition.